LIBRAS: LANGUAGE IN CONSTRUCTION, TEACHING IN (TRANS)FORMATION (PERcursos Linguísticos, 2024)
ABSTRACT: The Brazilian sign language, Libras, as we know it today, was built and idealized by the Brazilian deaf community and Deaf Studies researchers. In this work, I introduce one part about theoretical basis of my thesis in progress where I reflect on the period between the years 1980 and 2000 before the promulgation of the Law number 10.436/2002, also known as Law of Libras. The governmental language policy project for the diffusion of Libras in an institutional way reached widely across the national territory reaching places that it had never been before, like elementary and high schools, universities, law spaces and health, and artistic/cultural. I highlight the book Libras em Contexto has been one federal government initiative to Libras expansion across to Brazil. Considering a more plural and diverse perspective, I suggest in this article an inter(trans)cultural language education aligned with some texts based on decolonial theories, to Libras to achieve those deaf people who are on the sidelines. At the same time, this language education must respect and value people’s histories, languages, cultures, as without that they are turning invisible like they were, or have been, due to the colonial violence imposed on our society.KEYWORDS: Libras. Decoloniality. Language Education.
Keywords: Libras. Decoloniality. Language Education.